A Review on Response of Root System Architecture and Root Phenotypic for Biotic And Abiotic Stress - Wole Damena, Arega (Journal of Agronomy Research, 2023)
Root is has great role for plant adaptation and productivity of the agricultural crops as well as other plants by exploiting the soil resource thus, important for plant growth and development or main growth factors. Root system architecture is made up of structural features which exhibits great role in response to environmental stress, and critical to plant growth and development with sufficient root growth. Root system architecture has a central role in crop plants’ response to abiotic (soil microorganisms) and abiotic stresses like water stress, mechanical impedance. Root morphology can be affected by nutrient availability, osmotic stress, salinity, and light. Phenotyping root is one of the drought management tools as roots are more prone to drought conditions and play a signiﬁcant role in the plant’s life by extracting soil resources from deeper soil layers to carry on several metabolic functions in the plant’s body and its phenotyping helps to understand different root traits. Understanding interactions between roots and their surrounding soil environment is important to increase root growth, which can be improved through root phenotyping. In addition, knowing of the development and architecture of roots, as well its plasticity, holds thus great role for stabilizing the productivity under suboptimal conditions in the root environment
Keywords: Root System Architecture; Abiotic Stress; Drought; Salinity; Plant Growth